2018
DOI: 10.1002/cpsc.68
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Adipose Tissue–Derived Stem Cells: Enzymatic Digestion in Combination with Mechanical Distortion to Increase Adipose Tissue–Derived Stem Cell Yield from Human Aspirated Fat

Abstract: Mesenchymal stem cells (MSCs) are of great interest due to their properties of immune modulation, tissue regeneration, and multipotent differentiation. Future developments of clinical applications, however, require a higher yield of MSCs, lower number of passages of cells in culture, and shorter time from harvest to use. Optimization and standardization of techniques for mesenchymal adipose tissue–derived stem cell isolation offers solutions to current bottlenecks as a larger amount of MSCs can be isolated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Some authors, showed the ability to isolate and expand adipose-derived stromal cells in stirred bioreactor using Corning R Synthemax II microcarriers (Gadelorge et al, 2017), but the majority of the studies with AT MSC are focused in tissue regeneration and its immunomodulatory properties (Zhou et al, 2011;Madonna et al, 2015). Nevertheless, reports show improvements in isolation techniques than can further optimize the process of using AT MSC in xeno-free conditions (Francis et al, 2018;Alstrup et al, 2019;Lisini et al, 2019). Although we have established a serum-free and xeno-free microcarrier-based expansion of AT MSC using a commercially available formulation Santos et al, 2011;Carmelo et al, 2015), the cell adhesion (36 ± 5.2%) and maximal cell density (1.9 × 10 5 cells/mL) achieved were significantly inferior when compared to BM MSC expanded under the same conditions (95% and 3.6 × 10 5 cells/mL), highlighting the need to improve the expansion process of this specific cell source under xenogeneic(xeno)-free culture conditions (Carmelo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors, showed the ability to isolate and expand adipose-derived stromal cells in stirred bioreactor using Corning R Synthemax II microcarriers (Gadelorge et al, 2017), but the majority of the studies with AT MSC are focused in tissue regeneration and its immunomodulatory properties (Zhou et al, 2011;Madonna et al, 2015). Nevertheless, reports show improvements in isolation techniques than can further optimize the process of using AT MSC in xeno-free conditions (Francis et al, 2018;Alstrup et al, 2019;Lisini et al, 2019). Although we have established a serum-free and xeno-free microcarrier-based expansion of AT MSC using a commercially available formulation Santos et al, 2011;Carmelo et al, 2015), the cell adhesion (36 ± 5.2%) and maximal cell density (1.9 × 10 5 cells/mL) achieved were significantly inferior when compared to BM MSC expanded under the same conditions (95% and 3.6 × 10 5 cells/mL), highlighting the need to improve the expansion process of this specific cell source under xenogeneic(xeno)-free culture conditions (Carmelo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, harvesting large volumes of BM-MSCs is associated with increased donor-site morbidity [ 23 , 24 ]. Different buffers and culturing techniques can result in yield differences in AD-MSCs [ 25 , 26 ]. In general, AD-MSCs are metabolically active for longer durations, making them able to go through more replication cycles than BM-MSCs; however, no proposed mechanism has been given for this observation [ 13 , 27 , 28 , 29 ].…”
Section: Tissues Containing Mscsmentioning
confidence: 99%
“…The minced adipose tissue was then digested on an orbital shaker at 140 rpm using 0.1% collagenase type I (Sigma Aldrich, Darmstadt, Germany) at 37 • C for 1.5 h. In total, 300 µL of 0.1% collagenase were used per gram of fat. Thereafter, the fat mixture was centrifuged at 644× g for 5 min to obtain a cell pellet [3,23].…”
Section: Fat Harvest and Culture Of Mscsmentioning
confidence: 99%